Padrões Fractais: conectando Matemática e Arte - Rejane Waiandt Schuwartz Faria; Marcus Vinicius Maltempi (EccoS – Revista Científica)
The main aim in this paper is to introduce the concept of fractal pattern and its potential in teaching and learning of mathematical content, with emphasis on visual and artistic aspects. We explore the idea that both Math and Arts are linked to human activities with expressions derived from intelligence, wishes, ideas and needs of expression. These expressions lead us to the dynamism, rigor, creativity, aesthetics, harmony, symmetry and many other concepts that are present in Arts, Mathematics and Fractal Patterns. Self similarity and infinite complexity are visual properties of the Fractals Patterns that provide the feeling of surprise and the aesthetic contemplation of the regularities present in the apparent irregularity of these patterns.